COVID-19 vaccine online misinformation in Fiji: Preliminary findings - Romitesh Kant (Pacific Journalism Review, 2021)
Digital media, opens a vast array of avenues for lay people to effectively engage with news, information and debates about important science and health issues. However, they have also become a fertile ground for various stakeholders to spread misinformation and disinformation, stimulate uncivil discussions and engender ill-informed, dangerous public decisions. During the COVID-19 pandemic, antivaccination social media accounts are proliferating online, threatening to further escalate vaccine hesitancy. The pandemic signifies not only a global health crisis, it has also proven to be an infodemic characterised by many conspiracy theories. Prior research indicates that belief in health-related conspiracies can harm efforts to curtail the spread of a virus. This article presents and examines preliminary research findings on COVID-19 vaccine related misinformation being circulated on Fijian Facebook Forums.